The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1021/jacs.1c07107
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning the Micro-Environment to Optimize the Catalytic Activity of Enzymes Immobilized in Multivariate Metal–Organic Frameworks

Abstract: The artificial engineering of an enzyme's structural conformation to enhance its activity is highly desired and challenging. Anisotropic reticular chemistry, best illustrated in the case of multivariate metal−organic frameworks (MTV-MOFs), provides a platform to modify a MOF's pore and inner-surface with functionality variations on frameworks to optimize the interior environment and to enhance the specifically targeted property. In this study, we altered the functionality and ratio of linkers in zeolitic imida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 84 publications
2
77
0
Order By: Relevance
“…State-of-the-art MOFs are complex/multicomponent/multivariate MOFs prepared through various strategies, 131,320,332,334,336,337,351–360 possessing multiple active sites, which target synergistic/cooperative photocatalysis and catalysis and advanced tandem reactions.…”
Section: Classification Of Porous Materials and Their Active Sites Fo...mentioning
confidence: 99%
See 1 more Smart Citation
“…State-of-the-art MOFs are complex/multicomponent/multivariate MOFs prepared through various strategies, 131,320,332,334,336,337,351–360 possessing multiple active sites, which target synergistic/cooperative photocatalysis and catalysis and advanced tandem reactions.…”
Section: Classification Of Porous Materials and Their Active Sites Fo...mentioning
confidence: 99%
“…338 Photocatalyst-based MOF systems possess plentiful reactive sites and increased electron-hole pair lifetime (decrease in photogenerated charge recombination rate) and charge mobility compared to the traditional semiconductors. 340 State-of-the-art MOFs are complex/multicomponent/multivariate MOFs prepared through various strategies, 131,320,332,334,336,337,[351][352][353][354][355][356][357][358][359][360] possessing multiple active sites, which target synergistic/cooperative photocatalysis and catalysis and advanced tandem reactions.…”
Section: Strategies For Introducing Catalytic Moietiesmentioning
confidence: 99%
“…Thus, the hydrogen bonds of the framework could be adequately adjusted to be strong enough to interact with enzyme surface and generate an optimized conformation, albeit leaving untouched the structure of the buried catalytic triad. Ultimately, this allowed maintaining 99% enantiomeric excess of the products in several kinetic resolution reactions that were evaluated [136]. Within the same scope, Ruiz and co-workers, showed that depending on the type of carrier, and concomitantly immobilization method used and corresponding enzyme-enzyme and enzyme-surface interactions, the catalytic features of a psychrophilic lipase were modified.…”
Section: Carrier Composition and Immobilization Methodsmentioning
confidence: 98%
“…Considerable efforts have been devoted to constructing efficient enzyme‐immobilization systems through strategies such as adsorption, covalent bonding, crosslinking, using various materials (e.g., polymer, silica, metal oxide) as the matrix [10–18] . However, vast limitations still remain in this field, such as encapsulation of large‐size enzymes, substrate/product transfer issues caused by nonporous carriers, leaching or conformational change of enzymes during the immobilization process [19–22] . It is also of great challenge to elaborately design the immobilization systems to adapt the characteristics of enzyme/reaction or expediently fabricate the immobilized biocatalysts on a large scale [23] .…”
Section: Introductionmentioning
confidence: 99%